A CROSS-SECTIONAL STUDY ON PREVALENCE AND FACTORS ASSOCIATED WITH BURNOUT AMONG NURSES IN MULAGO NATIONAL REFERRAL HOSPITAL, KAMPALA-UGANDA. - Tumwesigye, Ambrose; Twinomujuni, Elias; Akampumuza, Davis; Abeneitwe, Editor; Niyonzima, Vallence (Student's Journal of Health Research Africa, 2025)
Background. Burnout is a condition that results from chronic stress characterized by depersonalization, emotional exhaustion, and diminished personal accomplishment. It has been a big hindrance to planning for health care services. Research has found that burnout causes poor performance on the job characterized by being absent and unexplained poor health status. This study determined the Prevalence and factors associated with burnout among Nurses in Mulago National Referral Hospital, Kampala-Uganda. Methodology. A descriptive cross-sectional survey was conducted among 273 randomly selected nurses from Mulago National Referral Hospital, Kampala. Quantitative data were collected using a self-administered questionnaire. Data analysis consisted of descriptive statistics and logistic regression at a 95% level of significance in Stata version 17. Results. The majority of the respondents were female 190(69.9%), 76.6% (209/273) of the respondents were aged 30 years and above, 52.0% (142/273) of the participants were Assistant nursing officers by profession and 87.9% (240/273) were Christians. More than half 54.2% (148) of respondents had high levels of burnout (≥42 Score) and most of them 117 (59.4%) agreed that ward arrangement and patient numbers are breaking. While 45.8% (125) reported low levels of burnout. The factors were: inappropriate Nurse-physician relationship (aOR 3.04, p Value 0.009) feeling that the job is controlled by administrators (aOR 2.26, p value 0.035), and Unsuitable working environment (aOR 2.44 (95%, p value 0.018). Conclusion More than a half of nurses in Mulago National Referral Hospital experienced high levels of burnout due to factors like Unsuitable working environment and inappropriate Nurse-physician relationship. Recommendations. The Ministry of Health should consider recruiting more nurses to reduce workload, especially in emergency units, improve on nurse-physician relationship, and assure nurses of their job security for those who feel threatened by the administrators.